2020
DOI: 10.1371/journal.pntd.0008848
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lipidomic analysis of Ascaris suum

Abstract: Ascaris is a soil-transmitted nematode that causes ascariasis, a neglected tropical disease affecting predominantly children and adolescents in the tropics and subtropics. Approximately 0.8 billion people are affected worldwide, equating to 0.86 million disability-adjusted life-years (DALYs). Exploring the molecular biology of Ascaris is important to gain a better understanding of the host-parasite interactions and disease processes, and supports the development of novel interventions. Although advances have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In S. mansoni , Ferreira et al ( 2014a ) reported the presence of phospholipids and triacylglycerols, with phosphatidylcholines (PCs) being the major lipids (Ferreira et al, 2015 ). Similarly, Wang et al ( 2020 ) putatively identified 587 lipids from the somatic tissue extract of Ascaris suum .…”
Section: Lipids Of the Excretory-secretory Products And Tissue Extrac...mentioning
confidence: 97%
See 1 more Smart Citation
“…In S. mansoni , Ferreira et al ( 2014a ) reported the presence of phospholipids and triacylglycerols, with phosphatidylcholines (PCs) being the major lipids (Ferreira et al, 2015 ). Similarly, Wang et al ( 2020 ) putatively identified 587 lipids from the somatic tissue extract of Ascaris suum .…”
Section: Lipids Of the Excretory-secretory Products And Tissue Extrac...mentioning
confidence: 97%
“…Over 500 putative metabolites, including lipids, have been reported from a single helminth species (Wang et al, 2018 , 2020 ; Wangchuk et al, 2019b ; Yeshi et al, 2020 ), yet their bioactivity remains largely unexplored. Currently, only 20–30% of the total metabolites are known, with 70–80% remaining unidentified due to limitations in identification protocols and helminth-specific compound libraries.…”
Section: Metabolic Pathways and Biosynthesismentioning
confidence: 99%
“…(2016) Ascaris suum Female adult UHPLC-MS/MS Targeted lipidomics (steroids) Ma et al. (2019a) L3-egg, L3-lung, L4, male and female adults, as well as organ system from male and female adults UHPLC-MS/MS Untargeted lipidomics Wang et al. (2020d) Haemonchus contortus L3, L4, adults UHPLC-MS/MS Untargeted lipidomics Wang et al.…”
Section: Mass Spectrometry-based Analytical Workflows For Lipidomic I...mentioning
confidence: 99%
“…Recently, we also investigated the lipidomes of key developmental stages/sexes as well as organ systems of A. suum using high throughput LC-MS/MS ( Wang et al., 2020d ). Approximately 600 lipid species belonging to 18 lipid classes were identified.…”
Section: Lipidomic Studies Of Parasitic Wormsmentioning
confidence: 99%
See 1 more Smart Citation